Educational inclusion in the social sciences: Didactic approaches and fundamental principles - Palacios Carrillo, Eliana (2025)
Today, education is facing challenges derived from changes in social reality, which requires rethinking didactics as a means to promote new forms of inclusion. This entails the need to develop alternatives that consolidate the principle of inclusion as a basis for quality education. In this sense, the article aims to analyze education from a didactic approach focused on inclusion. For this purpose, a qualitative methodology that integrated documentary review and interpretative action was used in order to describe and present results on the challenges faced by didactics when incorporating inclusive processes. It also highlights the importance of redefining the role of the teacher, approaching it from a new perspective that allows the construction of pedagogical strategies aimed at redefining didactic competence, considering both theory and practice in current educational contexts.